PRODUKTIVITAS DAN BIAYA ANGKUTAN KAYU DENGAN REL BAJA DAN REL KAYU - Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1988)
The paper presents  the result of a study  on the productivity  and cost of haulage on steel and wooden  rails.  The study was  conducted at  4 logging companies in  West  Kalimantan   during  year  1982.  There  were 2  methods of  log haulage observed, namely using locomotive and  manual  pushing.The  logging companies generally  used rail weighing  7 - 10 kg/m  and 5 x 7 cm wooden  rail. The distance between steel and  wooden  rails were  respectively 60  - 70  cm  and  60  cm  or  less.  The  crew  size  varied  from  8 to 12 men  for locomotive haulage consisting  of  12 - 16  lorries,  and  2 - 4 men/lorry for haulage on  wooden rail.  The  result  of  the haulage study  reveals also the productivity figures of respectively  156.9  m3 km/hour  and 2.4 m3 km/hour for the first and the second  methods mentioned   above.                                                                                            Log  transportation   on steel  rail  is safer for the labour compared  with  that on wooden  rail,  and the life of steel  rail is much   longer  than  that,  of  wooden rail.   Although   steel  rail is higher  in the  investment   cost  compared  with  woode'n  rail (Rp  14 - 21  million/km and Rp  2.35 million/km respectively), the average haulage cost per m3' km  is about  one-third  of the  latter  (Rp 80.1/m3 km  and Rp  254.4/m3 km respectively).